Characterization and Relative Quantitation of Wheat, Rye, and Barley Gluten Protein Types by Liquid Chromatography–Tandem Mass Spectrometry - Lexhaller, Barbara; Colgrave, Michelle L.; Scherf, Katharina A. (Frontiers in Plant Science, 2019)
The consumption of wheat, rye and barley may cause food hypersensitivities such as celiac disease (CD), non-celiac gluten/wheat sensitivity (NCGS) or wheat allergy. The storage proteins (gluten) are known as major triggers, but also other functional protein groups such as α-amylase/trypsin-inhibitors or enzymes are possibly harmful. Gluten is widely used as a collective term for the complex protein mixture of wheat, rye or barley and can be subdivided into the following gluten protein types (GPTs): α-gliadins, γ-gliadins, ω5-gliadins, ω1,2-gliadins, high- (HMW-GS) and low-molecular-weight glutenin subunits (LMW-GS) of wheat, ω-secalins, HMW-secalins, γ-75k-secalins and γ-40k-secalins of rye and C-hordeins, γ-hordeins, B-hordeins and D-hordeins of barley. GPTs isolated from the flours are useful as reference materials for clinical studies, diagnostics or in food analyses and to elucidate disease mechanisms. A combined strategy of protein separation according to solubility followed by preparative reversed-phase high-performance liquid chromatography (RP-HPLC) was employed to purify the GPTs according to hydrophobicity. Due to the heterogeneity of gluten proteins and their partly polymeric nature, it is a challenge to obtain highly purified GPTs with only one protein group. Therefore, it is essential to characterize and identify the proteins and their proportions in each GPT. In this study, the complexity of gluten from wheat, rye, and barley was demonstrated by identification of the individual proteins employing a discovery proteomics strategy involving liquid chromatography-tandem mass spectrometry (LC-MS/MS) of tryptic and chymotryptic hydrolysates of the GPTs. Different protein groups were obtained and the relative composition of the GPTs was revealed. Multiple reaction monitoring (MRM) LC-MS/MS was used for the relative quantitation of the most abundant gluten proteins. These analyses also allowed the identification of known wheat allergens or of CD-active peptides. Combined with functional assays, these findings may shed light on the mechanisms of gluten/wheat-related disorders and may be useful to characterize reference materials for analytical or diagnostic assays more precisely.